Work Environment and Competence on Satisfaction and Performance of in a Development Planning Agency - Paulus Liberthy Warisal; Agusthina Risambessy (Indonesian Journal of Multidisciplinary Science, 2022)
Physical or non physical work environment is an influential factor which is necessary to support the employees activities in finishing their jobs. This study aimed to analyze and examine direct effect of work environment on work satisfaction, indirect effect of work environment on employees performance through work satisfaction, direct effect of competence on work satisfaction, indirect effect of competence on employees performance through work satisfaction, and the effect of work satisfaction on work performance. This study was conducted at the Development Planning Agency in Maluku. The population of the study was 117 employees who were working for the Development Planning Agency in Maluku. Saturated sample technique was used in this study. Data was collected through interviews and questionnaires. Data was analyzed using path analysis. The descriptive results of the research showed that respondents provided good responses toward the work environment variable as it achieved 3.96 as the mean score. The mean score of competence variable was 3.92, of work satisfaction was 4.13, and of employees performance was 3.89. The results of statistical data analysis proved that work environment (such as comfortable rooms for work, good lighting, internet facility provision, good interaction among colleagues, good relationship between the supervisor and the subordinates) had a positive and significant direct effect on work satisfaction with significance value of 0.000 < 0.05. In addition, work environment had positive and significant indirect effect on employees performance through work satisfaction with significance value of 0.000 < 0.05.